ANALYSIS OF THE EFFECT OF EUCS VARIABLES ON USER SATISFACTION IN THE APPLICATION OF CEISA 4.0 AS AN ADMINISTRATIVE SYSTEM - Marwah, Siti; Prasojo, Bayu Hari; Pebrianggara, Alshaf; Almanfaluti, Istian Kriya (Transpublika Publisher, 2025)
This study analyzes the impact of EUCS (End-User Computing Satisfaction) variables on user satisfaction with the CEISA 4.0 administrative system at KPPBC TMP Juanda. This study aims to evaluate how various factors, including technical support, reporting features, and system usability, contribute to overall user satisfaction. Data were collected through a survey, and analysis used Structural Equation Modeling (SEM) to assess the relationship between the identified variables. Key findings indicated that users experienced satisfactory technical support, characterized by quick responses and effective solutions to problems. In addition, the system's excellent reporting features facilitate the generation of comprehensive and easy-to-understand reports, further increasing user satisfaction. The research also included validity and reliability tests, confirming that the constructs used in this study are valid and reliable for measuring user satisfaction. The results show that improving these factors can significantly increase user satisfaction with CEISA 4.0, ultimately leading to more efficient administrative processes. This research adds to a more profound comprehension of the elements that influence user satisfaction in administrative systems, as well as providing valuable insights for future development of similar technologies.